Protecting the ozone layer - Parson, Edward A. (Oxford University Press, 2003)
This book is the first comprehensive history of international efforts to protect the ozone layer, the greatest success yet achieved in managing human impacts on the global environment. Its arguments about how this success was achieved are both theoretically novel and of great significance for the management of other global problems, particularly global climate change. The book provides an account of the ozone-depletion issues from the first attempts to develop international action in the 1970s to the mature functioning of the present international regime